The association between testosterone and serum soluble klotho in the females: evidence from the NHANES database - Cao, Qi; Zhang, Jiani; Hao, Xiaohu; Du, Siyu; Ao, Lu; Zhu, Huili; Huang, Wei (Frontiers in Endocrinology, 2024)
Objective: This research aimed to elucidate the relationship between testosterone levels and serum soluble klotho (S-klotho) concentrations in females aged 40-79 years using the National Health and Nutrition Examination Survey (NHANES) dataset. Design: Associations between testosterone and S-klotho were assessed through multivariable linear regression methodologies, spanning nonadjusted, minimally adjusted, and fully adjusted models. Settings: The investigation was conducted as a cross-sectional analysis utilizing the NHANES database. Participants: From 20,146 NHANES participants between 2013 and 2016, 2,444 females met the stipulated inclusion and exclusion criteria.Results: Free androgen index (FAI) showcased a negative correlation with Sklotho levels across all regression models (nonadjusted: β -7.08, 95% CI -13.39--0.76; minimally adjusted: β -9.73, 95% CI -16.6--2.84; fully adjusted: β -7.63, 95% CI -14.75-0.51). Conversely, total testosterone did not exhibit significant associations with S-klotho across the models. In the nonadjusted model, estradiol was positively associated with S-klotho concentrations (β 0.14, 95% CI 0.05-0.23), but this significance was not retained in subsequent regression models.Conclusions: Findings suggest that in U.S. females aged 40-79 years, FAI negatively correlates with S-klotho concentrations, while there is the lack of significant associations for total testosterone and estradiol.